Violence Prevention Policy Practices in Schools: A Systematic Literature Review - M Fahmi Zakariyah; Desika Putri Mardiani; Muchamad Arif; Varia Virdania Virdaus; Yahya Raja Ado; Mochamad Nursalim; Wiwin Yulianingsih (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
prevention policies and practices in schools, focusing on the key factors that influence their effectiveness and the role of social, cultural and economic contexts. The approach used was Systematic Literature Review (SLR), analyzing 35 articles from highly ranked journals to synthesize evidence on the implementation and outcomes of school violence prevention policies. The review showed that key elements of effective policies include staff training, restorative approaches, mental health support, and inclusive policy design. In addition, social norms, cultural sensitivity and economic resources were found to have a significant influence on the successful implementation of the policy. This study provides practical implications in the form of recommendations to strengthen school leadership, increase community engagement, and prioritize mental health services in violence prevention strategies. This study contributes to the literature by offering a detailed framework for developing more effective and adaptive violence prevention policies, while emphasizing the importance of an approach that is responsive to the local context. The findings of this study offer a novel contribution by integrating contextual factors such as social, cultural and economic factors into the development of a school violence prevention framework, which is often overlooked in previous studies.